Listening styles of ESL instructional leaders in institutions of higher learning / Nur Zahira Samsu Zaman @ Taufiq - Samsu Zaman @ Taufiq, Nur Zahira (2012)
Educational leadership for the 21st century puts a critical demand on teachers to become effective Instructional Leaders for successful student learning. Henceforth, this study was conducted with the aim to identify the listening styles of ESL instructional leaders in institutions of higher learning in Malaysia. The descriptive study comprised 62 ESL lecturers from three institutions of higher learning in Malaysia. The study employed a mixed method research design where data were collected via a questionnaire survey and in-depth semi-structured interviews. The quantitative data were analysed using SPSS version 17 for Windows while qualitative data were analysed deductively and inductively based on the research questions in order to trace emerging patterns. The validity and reliability of the instruments was established through experts’ opinions and a pilot study. The overall reliability was established at 0.717 alpha level. The findings revealed that People-Oriented listening style was the most preferred listening style among ESL instructional leaders followed by Content-Oriented listening style, Action Oriented listening style and Time-Oriented listening style. Findings also indicated that there were no significant differences in listening styles between males and females and ESL instructional leaders in IHLs. The analysis also depicted that there was no significant difference in listening styles between the novice and experienced ESL instructional leaders. Nevertheless, there was a significant difference in the mean score for Action-Oriented listening style between novice and experienced ESL instructional leaders. External distractions and environment, language and sentence organization, communication style, personal emotion and attitude, non-verbal cues and cultural differences were some of the main challenges faced by ESL instructional leaders. The findings imply that educational leaders need to be aware of effective listening styles as it can enhance the teaching and learning process. It may also serve as a platform to motivate instructional leaders in tertiary institutions to productively change their personal listening style into a more appropriate listening behaviour which in turn may enhance their communication aptitude.